Major Histocompatibility Complex Class II Dextramers: New Tools for the Detection of antigen‐Specific, CD4 T Cells in Basic and Clinical Research. (November 2015) - Massilamany, C.; Krishnan, B.; Reddy, J.
Abstract The advent of major histocompatibility complex (MHC) tetramer technology has been a major contribution to T cell immunology, because tetramer reagents permit detection of antigen‐specific T cells at the single‐cell level in heterogeneous populations by flow cytometry. However, unlike MHC class I tetramers, the utility of MHC class II tetramers has been less frequently reported. MHC class II tetramers can be used successfully to enumerate the frequencies of antigen‐specific CD4 T cells in cells activated in vitro, but their use for ex vivo analyses continues to be a problem, due in part to their activation dependency for binding with T cells. To circumvent this problem, we recently reported the creation of a new generation of reagents called MHC class II dextramers, which were found to be superior to their counterparts. In this review, we discuss the utility of class II dextramers vis‐a‐vis tetramers, with respect to their specificity and sensitivity, including potential applications and limitations.